Rat dissecting kit / Noriantie Ibrahim, Cik Jamaliah Abd Manaf and Lock Shu Ping - Ibrahim, Noriantie; Abd Manaf, Cik Jamaliah; Lock, Shu Ping (Universiti Teknologi MARA, Kedah, 2019)
Rat Dissecting Kit (RDK) is a simulation model in anatomy learning and as alternative evaluation tools for dissecting skills. The use of RDK meets the 21st century learning approach which integrates simulation with ICT technologies. RDK is the first prototype used in matriculation program. Cost of care and removal of residual rats after dissection also can be minimized. Students can explore mammal anatomy effectively. In addition, it serves as engagement kit to improve student’s dissecting skills before they perform actual dissection. The usage of RDK allows learning sessions to be exciting and fun as it integrates new technologies and simulations. Impact usage for students is in improving the handling skills in dissecting class. It’s enhances student’s motivation during learning and encourages collaboration among students. Furthermore, it’s also develop self-access learning and leadership skills of students. RDK can use as alternative approach in the designing teaching and learning activities. It’s also improve effectiveness in classroom management. Lecturers being more confident and enjoyable when handling demonstration on dissecting procedures. The atmosphere of learning is more vibrant and inclusive. The use of RDK also demonstrates the sensitivity to the ethical issues of laboratory rat and raise awareness by reducing the number of rat using in dissection experiment. RDK is a suitable engagement kit for dissection and anatomy class for secondary school and pre university program. It has potential alternatives for replacing the using of lab animal in dissection. Therefore, it can be commercialized all over the world in anatomy learning.